2022
DOI: 10.1016/j.psj.2021.101514
|View full text |Cite
|
Sign up to set email alerts
|

Body weight, organ development and jejunal histomorphology in broiler breeder pullets fed n-3 fatty acids enriched diets from hatch through to 22 weeks of age

Abstract: Dietary long chain polyunsaturated n-3 fatty acids ( n-3 FA ) may be beneficial to broiler breeder ( BB ) development. Therefore, the effects of feeding sources of docosahexaenoic acid ( DHA ) and α-linolenic acid ( ALA ) from hatch through to 22 weeks of age ( woa ) on growth, organ weight, and jejunal histomorphology were investigated. A total of 588-day-old Ross × Ross 708 BB were reared on one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Due to the jejunum's unique features, i.e., efficient nutrients absorption via the largest surface area [23], and efficient nutrient translocation via active vascular system of villi [24], nutrient absorption/ intake mainly occurs in the jejunum. The jejunal histomorphology is a good indicator for digestive/absorptive ability [25]. It has also been reported that jejunal microbiota considerably contributes to the nutrient uptake and utilization in broilers [26].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the jejunum's unique features, i.e., efficient nutrients absorption via the largest surface area [23], and efficient nutrient translocation via active vascular system of villi [24], nutrient absorption/ intake mainly occurs in the jejunum. The jejunal histomorphology is a good indicator for digestive/absorptive ability [25]. It has also been reported that jejunal microbiota considerably contributes to the nutrient uptake and utilization in broilers [26].…”
Section: Introductionmentioning
confidence: 99%
“…Some effects of FFF or YB were noted on growth performance in some phases in the present study but no effects in the overall (0–16 woa). We previously reported that feeding 2.3% FFF did not have effects on BW in egg type ( Akbari Moghaddam Kakhki et al, 2020 ) or broiler breeder ( Thanabalan and Kiarie, 2021 ) pullets. Another study observed no effect of feeding 5% to 10% flaxseed on pullet growth ( Arshami et al, 2010 ).…”
Section: Discussionmentioning
confidence: 97%
“…A flock with higher uniformity at point of lay attains peak egg production earlier and produces more and heavier eggs in lifetime and will peak higher than a nonuniform flock due to varying degrees of maturity ( Hudson et al, 2001 ; Leeson and Summers, 2005 ). While there are little scientific data available, pullet flock with ≤10% BW CV at sexual maturity is considered uniform ( Arrazola et al, 2019 ; Thanabalan and Kiarie 2021 ). The observed BW CV in the present study was well below 10%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, BW increased as the hens aged, regardless of TM source, and was similar to the target BW ( Aviagen, 2021b ). Achieving the desired BB target BW for age is a primary benchmark for evaluating the quality of pullets ( Thanabalan and Kiarie, 2021 ; Maina et al, 2024 ). Producers aim to ensure that 80% of the pullets fall within the designated weight ranges.…”
Section: Discussionmentioning
confidence: 99%